ANALISIS PENGARUH PEMANFAATAN TEKNOLOGI INFORMASI DAN BUDAYA KERJA TERHADAP KINERJA PEGAWAI KANTOR PERTANAHAN KABUPATEN KEBUMEN DENGAN MOTIVASI SEBAGAI VARIABEL MODERASI - Suprayitno, Budi Purnomo, Amin Wahyudi & (Universitas Slamet Riyadi, 2016)
The purpose of this study are to analyze: 1) effect of use information technology on employees performance, 2) effect of work culture on employees performance, 3) effect of motivation on employees performance, 4) effect of use of information technology on employees performance with motivation as moderation variables, 5 ) effect of work culture on employees performance with motivation as moderation variables. The research location in Kantor Pertanahan Kabupaten Kebumen. The study population of all employees 55 and overall employee used as a sample with technique census. Types of data used quantitative and qualitative data. Source of data used primary data and secondary data. Data collection techniques used the documentation, observation and questionnaires. Analysis techniques used test validity, test reliability test classic assumptions, multiple linear regression, t test, F test, the coefficient of determination and test the difference in absolute. The results showed that the use of information technology had a significant effect on employees performance Kantor Pertanahan Kebumen District. Work culture had a significant effect on employees performance Kantor Pertanahan Kebumen District. Motivation had a significant effect on employees performance Kantor Pertanahan Kebumen District. The use of information technology had a significant effect on employees performance Kantor Pertanahan Kebumen District with motivation as moderation variables. Work culture had a significant effect on employees performance Kantor Pertanahan Kebumen District with motivation as moderation variables. Keywords: use of information technology, work culture, motivation and performance.